THE INFLUENCE OF TRANSPORT INFRASTRUCTURE ON THE ECONOMIC DEVELOPMENT OF REGIONS, ASSESSMENT OF THE EFFICIENCY OF ROAD MANAGEMENT - GRIN, Andriy; TOLOK, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article examines the impact of transport infrastructure on the economic development of regions, with a special focus on assessing the efficiency of road management. Modern transport infrastructure is a key factor that determines the pace of socio-economic growth of regions, ensuring the integration of national economies into the global market, stimulating investment and facilitating the creation of new jobs. The impact of transport networks covers various aspects of regional development, including increased mobility of the population, reduced transportation costs, and improved access to goods and services, which in turn increases the competitiveness of regions. However, road management faces a number of challenges, such as insufficient funding, deteriorating infrastructure, inefficient management processes, and environmental issues. The article analyzes the latest research and publications in this area, which allows identifying the main trends and challenges faced by the road sector. In particular, the article considers the impact of transport infrastructure on regional GDP, employment, entrepreneurship development and general living standards. The article highlights the main shortcomings in the management of the road sector, in particular, the insufficient use of modern technologies, the lack of an integrated approach to planning and development of transport networks, and the absence of long-term strategic planning. Based on the analysis, the author proposes a comprehensive approach to assessing the effectiveness of transport infrastructure management, which includes the use of quantitative and qualitative assessment methods, as well as taking into account socio-economic, environmental and financial aspects. The article also provides recommendations for improving the efficiency of road management, in particular, through the introduction of innovative technologies, development of effective financing mechanisms and modernization of existing infrastructure. In addition, the article outlines the prospects for further research in this area, focusing on the need to develop new management and evaluation methods that will increase the efficiency of transport resources and ensure sustainable development of regions in the face of growing economic challenges.